Intervenções educativas e medicamentosas para controle pressórico em transplantados renais baseadas no uso da monitorização ambulatorial da pressão arterial - Rebelo, Rafael Naufel de Sá (2022)
Arterial hypertension (AH) after kidney transplant (AKT) is correlated with severe cardiovascular and renal outcomes, such as kidney function loss, decreased graft survival, and high mortality rates. Manual office blood pressure (MOBP) values of kidney transplant recipients (KTR) are usually different from those obtained by systematic methodologies like Ambulatory Blood Pressure Monitoring (ABPM). Additionally, there is a significant prevalence of nocturnal non-dipping and blood pressure, white coat hypertension (WCH), and masked hypertension (MH). The goal of the present study was to evaluate the influence of educational and therapeutic actions on blood pressure control in KTR. The evaluation was performed by comparing pre-and post-intervention MOBP and ABPM measurements of individuals from the AKT outpatient clinic of a teaching hospital. It is an experimental, observational, prospective, and interventional cohort study. We included 33 adult patients with an average age of 46.8 years, hypertensive and non-diabetic. 53.8% of the study group had received organs from deceased donors. Data collection tools included a sociodemographic and clinical survey, three routine medical appointments at 2, 4, and 6 months to collect the standardized blood pressure measurement, and a lifestyle changes (LC) program. Additionally, the drugs were adjusted according to the 24 hours ABPM results. After 6 months, the test was repeated for the 26 patients who remained in the study. A paired t-test was used to evaluate the difference between the initial and the three follow-up evaluations. The impact of LC, the perception of symptoms, and the clinical assessment were evaluated using Student's t-test for BP indicators, and Fisher's exact test was used for the remaining comparisons between categorical variables. We observed that the ambulatory evaluation presents mean values higher than those obtained by the ABPM test (p<0.05) for systolic and diastolic values. ABPM results indicated that 4 out of 10 patients had an abnormal pressure curve, with a high prevalence of WCH (46.1%), and more than 90% of the participants did not show nocturnal dipping. The association of drug adjustments and LC was the most prevalent intervention was, comprising 88% of the proposed interventions; 8% of the patients required only LC guidelines and only 4% of the participants did not require any interventional action. The ambulatory diastolic BP values significantly decreased after 6 months of follow-up (p = 0.040). However, this good result was not repeated for ABPM. Patients were more likely to follow the diet changing program (69,3%) than the physical activity program (34.6%). Dietary change was associated with a significant reduction of mean systolic BP, measured by ABPM while awake and asleep. Patients who did not change their dietary habits showed an increase in this indicator. Hence, the study allowed us to verify the high prevalence of AH, diagnose the different AH phenotypes using ABPM, and implement personalized actions addressing clinical, behavioral, and drug-related aspects. These actions proved to be effective after a 6- moths follow-up. The actions could be more effective in larger sample size and with a longer follow-up. The results show the importance of ABPM as a strategy for BP followup in KTR